TRANSFORMATION OF ECONOMIC DEVELOPMENT OF KAZAKHSTAN IN THE CONDITIONS OF MODERN REALITIES - Zhurynov G.M.,; Abylkasym A.B.,; Sabenova B.N.,; Maulenkulovа G.E.,; Erzakova S.O., (Academic Journal of Physical and Chemical Sciences, 2020)
The article examines the features of the fourth industrial revolution and the place that characterizes the transformational concept of modern society in a series of other sociological theories. The published revolution is the result of the latest advances in information and communication, biotechnology, robotics, and artificial intelligence. Modern requirements of digitalization at the present time: compatibility (compatibility), virtualization, decentralization, and real-time operation. Cyber-physical systems, cloud computing and big data technologies, business on the Internet, virtual and horizontal integration, virtualization and «digitization» of all processes of value chain formation. Kazakhstan seeks to become not only an industrially developed country, but also a postmodern country, but today it is a postmodern state, primarily of modern man. Many developed countries and business giants are active participants in the fourth industrial revolution: government programs, business communities, and non-profit organizations were created to remove barriers to creating industry 4.0. The fourth industrial revolution is a predictable event, mass introduction of cyber-physical systems in production, satisfaction of human needs, including LIFE, Work and leisure. Changes cover various aspects of life: the labor market, environment, political systems, technological regime, human personality, and others. Due to the fact that improving the quality of life comes at the expense of economic efficiency and attractiveness, industry 4.0 performs it at the risk of increasing instability and possible collapse of the world system, so its attack is considered difficult for humanity to react.